2023
DOI: 10.1371/journal.pone.0288723
|View full text |Cite
|
Sign up to set email alerts
|

Antivenom preclinical efficacy testing against Asian snakes and their availability in Asia: A systematic review

Abstract: Background Cross-neutralizing strategy has been applied to improve access to antivenoms, a key to reducing mortality and disability of snakebite envenoming. However, preclinical studies have been conducted to identify antivenoms’ cross-neutralizing ability when clinical studies may not be considered ethical. Therefore, this study aimed to identify and summarize scattered evidence regarding the preclinical efficacy of antivenoms against Asian snakes. Methodology/Principle findings In this systematic review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Interestingly, Thai neuro-polyvalent antivenom, raised against elapid species venoms (i.e., Ophiophagus hannah , Naja kaouthia, Bungarus candidus , and Bungarus fasciatus ), was able to partially protect against the pre-synaptic neurotoxic effects of D. siamensis venom. There has not been much investigation into the effects of Thai neuro-polyvalent antivenom against viperid venoms [ 45 ]. However, it was previously suggested that the cross-neutralising ability of Thai neuro-polyvalent antivenom against pre-synaptic toxins was a result of common antigenic regions shared across species [ 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Thai neuro-polyvalent antivenom, raised against elapid species venoms (i.e., Ophiophagus hannah , Naja kaouthia, Bungarus candidus , and Bungarus fasciatus ), was able to partially protect against the pre-synaptic neurotoxic effects of D. siamensis venom. There has not been much investigation into the effects of Thai neuro-polyvalent antivenom against viperid venoms [ 45 ]. However, it was previously suggested that the cross-neutralising ability of Thai neuro-polyvalent antivenom against pre-synaptic toxins was a result of common antigenic regions shared across species [ 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%